The Relationship Between Sleep Quality and Emotion Regulation on Academic Performance of High School Students - Utomo, Rizky Amelia; Rini, Amanda Pasca; Matulessy, Andik (Kirana Publisher (KNPub), 2025)
This study aims to examine the relationship between sleep quality, emotion regulation, and academic performance among high school students. Learning is a vital process in developing students' skills, knowledge, and attitudes, with academic performance serving as a key indicator of success. High school students are in their adolescent phase, which is marked by physical, psychological, and social changes, as well as academic pressures that can affect their academic performance. One factor that may influence academic performance is sleep quality, which can impact concentration, memory, and mental health. On the other hand, effective emotion regulation can help students cope with academic stress and enhance their performance. This research was conducted to analyze whether sleep quality and emotion regulation influence the academic performance of high school students. The results showed no significant relationship between sleep quality and emotion regulation on students’ academic performance, with a significance value of 0.151 (p < 0.05). This indicates that other factors such as family support, motivation, and learning strategies may play a more dominant role in influencing students' academic performance. This study suggests that future research should consider the dynamic interplay among these factors and adopt a more in-depth approach to explore other variables that may affect students’ academic outcomes.